An animal in the philosophy of morality - Dyk, Wiesław (Studia Ecologiae et Bioethicae, 2004)
The discussion about the rights of animals is always up-to-date. The dichotomy division into philoanimalists and philohominists, although reasonable, is not satisfactory to everyone. It is too strongly associated with the division into people and things in Roman law. To avoid this association in the context of biocentric trends in ecological ethics, accomplishments of evolutionary psychology and the concept of animal welfare, it is suggested that a third moral dimension dealing with creatures with highly developed nervous system be introduced between moral objectivity of creatures with high perception and moral subjectivity of people - creatures characterized by self-awareness and reflexive awareness. Human beings on the one hand are responsible for recognizing their rights given by nature and on the other hand, they are obliged to create a law to protect themselves.